Towards Activation or Inactivation? Migrants’ Experiences of Encounters with the Swedish Public Employment Service - Maja Lilja; Hanna Li Kusterer; Sven Trygged (Nordic Journal of Migration Research)
Sweden has long pursued activation policies, particularly towards vulnerable groups in the labour market, with the Swedish Public Employment Service (PES) being the main agent of these policies. Recent cutbacks and organisational changes within the PES have significantly altered the support offered, particularly affecting migrants with low education and little work experience. This study investigates how these migrants experience encounters with the PES after the initial establishment period. A total of 23 refugees, mostly women, participated in semi-structured interviews that were analysed thematically. The interviewees struggled with job applications and requested personal encounters with the PES’s caseworkers, which was often denied. Classification played a role in relation to support from the PES; for example, it seemed that activities offered were based on gendered classifications, limiting some of the women. Furthermore, despite the activation policies, we discerned a risk of becoming inactive, especially because some interviewees believed that they should wait to be contacted by the PES to be offered a job or job-related activity. This calls for a different approach by the PES with more flexibility, practical support and opportunities for in-person meetings.